Kinetics of potassium release and fixation in some soils of Ogun State, Southwestern, Nigeria as influenced by organic manure - A. A. Taiwo; M. T. Adetunji; J. O. Azeez; K. O. Elemo (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The study investigated the effects of poultry and goat manures on the kinetics of potassium fixation and release in some sandy loam and loamy soils of Ogun State, Nigeria. Methods The treatments consisted of poultry and goat manures applied at 25 g and 100 g/5 kg soil set in completely randomized design with three replicates. Potassium fixation and release kinetics were computed from the analytical data. Results Experimental soils was sandy, slightly acidic, low in nutrients with 80% fixed potassium. However, manure application resulted in 74% reduction of the amount of K fixed by the soils. Elovich and power functions had the best fit for K released in soils treated with goat manure. The K release pattern in poultry manure-amended soil is best described by the parabolic diffusion, Elovich, and power functions, while the first-order equation described K release in soils treated with cattle manure. The potassium release rate constant correlated positively with K uptake. Conclusion The ability of the studied soils to fixed K was reduced with the application of organic manures. Potassium fixation decreased with increase in organic manure rates, 100 g/5 kg soil tends to be the optimum rate, and poultry manure had greater effect on the fixing and releasing power of K.